Frontline. Exodus [videorecording (DVD)] - Lyman, Will, 1948-; Bluemel, James (PBS Distribution, 2017)
The first-person stories of refugees and migrants fleeing war and persecution for Europe. Told through camera-phone footage filmed by the families themselves as they leave their homes on dangerous journeys seeking safety and refuge.